Humanistic Integration in Pesantren Education: Enhancing Moral and Social Character at Pondok Pesantren Lirboyo - Mukhlisin Mukhlisin; Abdurrahman Atsa’lawi (TA'DIB: Jurnal Pendidikan Agama Islam, 2026)
This study investigates the integration of humanistic values into Islamic education at Pondok Pesantren Lirboyo and analyzes its influence on students’ character formation. The research responds to the need for harmonizing classical pesantren traditions with contemporary humanistic pedagies that prioritize student-centered learning, critical inquiry, empathy, and holistic development. Employing a mixed-methods design, data were gathered through in-depth interviews with 15 teachers and 30 students, structured observations, document analysis, and statistical testing using ANOVA to measure differences in character outcomes across instructional models. Findings reveal that the deliberate incorporation of dialogue-based instruction, recognition of individual potential, and ethical modeling significantly strengthens students’ moral reasoning, social responsibility, and spiritual awareness. Learners exhibit enhanced interpersonal competence, stronger self-confidence, and greater ability to contextualize Islamic teachings within modern societal challenges. The pesantren demonstrates that adaptive pedagogical strategies and inclusive learning environments can sustain traditional scholarship while embracing humanistic principles. This study affirms that humanistic values reinforce rather than undermine Islamic educational foundations. It offers a replicable framework for pesantren reform, highlighting how institutions can modernize teaching practices without compromising theological authenticity, thereby cultivating compassionate, reflective, and socially responsive graduates.